Evaluation of Computer Training Programs Using Models Kirkpatrick to Increase the Competency Capacity of PerGunu Teachers - Ihsan Mustofa; Heri Kuswara (Nidhomul Haq, 2023)
Computers have very multi-tasking functions. Computers can help complete various jobs, one of which is that they can be used in the teaching and learning process. With the sophistication of hardware and software on computers, teachers can present attractive, interesting, and fun learning methods and models. Unfortunately, not all teachers can make the most of computers as a solution in their teaching and learning process. One of them happened to teachers who were members of the Nahdlatul Ulama Teachers' Association (Pergunu) in Lampung Province. Therefore, the Regional Board of the Nahdlatul Ulama Teachers Association of Lampung Province has carried out computer training program activities for Gunu teachers. To determine the extent to which the success of this training can be felt by the participants, researchers conducted research on this computer training program using the Kirkpatrick model or what is known as the Kirkpatrick Four Levels Evaluation Model, namely evaluating the effectiveness of Kirkpatrick's training program by evaluating training programs based on four stages of evaluation, namely: 1) reaction, 2) learning, 3) behavior, and 4) results. This evaluation was carried out as an effort to improve computer training programs in the future so as to be able to increase the competency capacity of teachers in optimizing computers as a means of successful learning. The results of the research that has been carried out on this Computer Training Program, meanwhile, show that participants get the benefits to be applied in the learning process.